2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346472
|View full text |Cite
|
Sign up to set email alerts
|

No surprise - fixed sequence event-related potentials for brain-computer interfaces

Abstract: Abstract-Introduction: In the field of Brain-Computer Interfaces (BCI), the original two-class oddball paradigm has been extended to multiple stimuli with balanced probabilities and random presentation sequences. Exploiting the differences between standard and deviant ERP responses, these multi-class paradigms are suitable for communication and control. Methods: The present study investigates the effect of giving up the randomness of stimulation sequences in favor of a repeated, predictable pattern. Data of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These restrictions do not apply to many kinds of real music. However, as stated before, abandoning the random sequences of an oddball paradigm and turning to more musical, and hence more predictable, structures is viable possibility as suggested by recent evidence on BCI classification using fixed sequences [33]. Furthermore, the complexity of the musical piece (by increasing the number of instruments and/or number of patterns per instrument) can probably be further increased.…”
Section: Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…These restrictions do not apply to many kinds of real music. However, as stated before, abandoning the random sequences of an oddball paradigm and turning to more musical, and hence more predictable, structures is viable possibility as suggested by recent evidence on BCI classification using fixed sequences [33]. Furthermore, the complexity of the musical piece (by increasing the number of instruments and/or number of patterns per instrument) can probably be further increased.…”
Section: Limitationsmentioning
confidence: 96%
“…The arbitrariness of the deviant patterns within the flow of music to some extent violates the musical structure, which, especially in Pop music, is simple, repetitive and therefore highly predictable. However, recent evidence demonstrates that switching from random sequences to fixed sequences does not hinder performance and that it can, on the contrary, even improve it [33]. Thus, it appears to be possible to make the musical oddball paradigm more musical by abandoning the classical oddball paradigm.…”
Section: Towards a Musical Bcimentioning
confidence: 99%
“…A sequence is a burst of trials that present several symbols (the entire alphabet or a carefully selected subset) in RSVP mode. During the presentation of a sequence, currently restricted to not present any symbol more than once, the symbols are ordered randomly for the purpose of strengthening the response for the intended symbol; however, recent evidence from auditory P300 BCIs indicate that randomization may not be crucial for successful operation [33]. The selection of a single symbol in the typing process occurs in an epoch , a period that consists of one or more sequences depending on when sufficient confidence is built based on the language evidence and accumulated multiple EEG evidence for candidate symbols.…”
Section: Rsvp Keyboard Testbedmentioning
confidence: 99%
“…Tangermann M studied the effect of fixed stimulus sequence on the repeated and predictable mode of auditory BCI. The results showed that the effect of fixed sequence was even improved compared with random sequence [28].…”
Section: Introductionmentioning
confidence: 99%